Infância, arte de governo pedagógica e cuidado de si - Pagni, Pedro Ângelo [UNESP] (My University, 2010)
This assay recoups the original direction of infantia to question the modern ambitions of its full government by means of the pedagogical art, in modernity, and to analyze its potential of resistance, in the present time, arguing the possibilities of this if to reconvert into praxis that the care of itself requires and of that assumed being as a debt on the part of the educators. For this, we will appeal to the Foucault concepts of governmentalization and of care of itself and to the Lyotard notion of debt it stops with infancy. Of this theoretician-conceptual perspective, we wait to offer some tracks so that, as educators, let us think the care with this another one, in the pedagogical art, from critical the philosophical one to the abuses of the power and the socratics recommendation on the on the care of itself.

Este ensaio recupera o sentido original da infância para problematizar as ambições modernas de seu pleno governo por meio da arte pedagógica, na modernidade, e para analisar o seu potencial de resistência, na atualidade, discutindo as possibilidades desta se reconverter em práxis que requer o cuidado de si e daquela ser assumida como uma dívida por parte dos educadores. Para isso, recorreremos aos conceitos foucaultianos de governamentalização e de cuidado de si e à noção lyotardiana de dívida para com a infância. Dessa perspectiva teórico-conceitual, esperamos oferecer algumas pistas para que, como educadores, pensemos o cuidado com esse outro, na arte pedagógica, a partir da crítica filosófica aos abusos do poder e da recomendação socrática sobre o cuidado de si.
Infancy, pedagogical art of governament and care of itself exactly
Keywords: Infância; governamentalização; cuidado de si; Experiência; Foucault